Human centric sensing by android phone - Cheng, Edward Dehua. (2013)
Existing indoor localization systems mostly require support from external infrastructures, especially WiFi hotspots or digitized floor maps, but we believe that an infrastructureless design is both desirable and possible. To this end, we propose our infrastructureless indoor localization system, a crowdsourced localization system exploring the indoor geomagnetism variance.